"I'd Have Divorced My Husband If Not for Korean Dramas" – Vietnamese Women's Consumption of Television Romance and Melancholia. Issue 3 (3rd July 2022) - Gammon, Thi
ABSTRACT: Drawing on the Freudian concept of melancholia and David L. Eng and Shinhee Han's contemporary approach to the concept, this article discusses how Vietnamese married women consume romantic South Korean television dramas as a means to deal with unacknowledged and unresolved loss, or the psychic condition of melancholia. Through a case study of melancholia in a female research participant and a discussion of Vietnamese women's marital lives, the article proposes two arguments. First, romantic consumption can be a private way for Vietnamese married women suffering from restricted freedom due to societal overemphasis on their familial duties to cope with melancholia. Second, the mass romantic culture, as a melancholic genre, allows married women to collectively mourn lost emotions such as the feeling of being young and being in love. The article makes a theoretical contribution by utilising Freud's melancholia and Eng and Han's contemporary approach to the concept for its empirical research. It also enriches an academic understanding of melancholia through its application of the concept to married women's psychic lives within a contemporary Vietnamese context.